Noble metal high entropy alloys - Sohn, Sungwoo; Liu, Yanhui; Liu, Jingbei; Gong, Pan; Prades-Rodel, Silke; Blatter, Andreas; Scanley, B. Ellen; Broadbridge, Christine C.; Schroers, Jan (Scripta Materialia, 2017)
A series of noble metal high entropy alloys with up to six constituent elements has been produced by casting. PtPdRhIrCuNi forms single-phase face-centered cubic solid solution, and its stability is confirmed by annealing experiments. This alloy deforms homogeneously to ~30% to a high ultimate compression strength of 1839MPa. We discuss rules for the formation of single-phase solid solution.
Keywords: Annealing experiments; Compressive properties; Compressive property; Constituent elements; Entropy; FCC structure; Face-centered cubic; Fcc structures; High entropy alloys; Phase stability; Precious metals; Single phase; Solid solution; Solid solutions; Ultimate compression; dept.phy